Fixed-Duration Ibrutinib-Venetoclax in Patients with Chronic Lymphocytic Leukemia and Comorbidities - Kater, Arnon P; Owen, Carolyn; Moreno, Carol; Follows, George; Munir, Talha; Levin, Mark-David; Benjamini, Ohad; Janssens, Ann; Osterborg, Anders; Robak, Tadeusz; Simkovic, Martin; Stevens, Don; et al. (NEJM evidence, 2022)
BACKGROUND: GLOW is a phase 3 trial evaluating the efficacy and safety of ibrutinib-venetoclax in older patients and/or those with comorbidities with previously untreated chronic lymphocytic leukemia (CLL). METHODS: We randomly assigned (1:1) patients 65 years of age or older or those 18 to 64 years of age who also had a Cumulative Illness Rating Scale (CIRS) score greater than 6 (CIRS scores range from 0 to 56, with higher scores indicating more impaired function of organ systems) or creatinine clearance of less than 70 ml/min, to ibrutinib-venetoclax (3 cycles ibrutinib lead-in, then 12 cycles ibrutinib-venetoclax) or chlorambucil-obinutuzumab (6 cycles). The primary end point was progression-free survival (PFS) assessed by an independent review committee. Secondary end points included undetectable minimal residual disease (uMRD), response rates, and safety. RESULTS: This study enrolled 211 patients, with 106 randomly assigned to ibrutinib-venetoclax and 105 to chlorambucil-obinutuzumab. With a median follow-up of 27.7 months, there were 22 PFS events for ibrutinib-venetoclax and 67 events for chlorambucil-obinutuzumab. PFS was significantly longer for ibrutinib-venetoclax than for chlorambucil-obinutuzumab (hazard ratio, 0.216; 95% confidence interval [CI], 0.131 to 0.357; P<0.001). The improvement in PFS with ibrutinib-venetoclax was consistent across predefined subgroups, including patients 65 years of age or older or with a CIRS score greater than 6. The best uMRD rate in bone marrow by next-generation sequencing was significantly higher for ibrutinib-venetoclax (55.7%) than for chlorambucil-obinutuzumab (21.0%; P<0.001). The proportion of patients with sustained uMRD in peripheral blood from 3 to 12 months after end of treatment was 84.5% for ibrutinib-venetoclax and 29.3% for chlorambucil-obinutuzumab. Four patients treated with ibrutinib-venetoclax required subsequent therapy compared with 27 patients receiving chlorambucil-obinutuzumab (hazard ratio, 0.143; 95% CI, 0.050 to 0.410). Adverse events grade 3 or greater occurred for 80 (75.5%) and 73 (69.5%) patients receiving ibrutinib-venetoclax and chlorambucil-obinutuzumab, respectively, with neutropenia being most common in both arms (37 [34.9%] and 52 [49.5%]). There were 11 (10.4%) and 12 (11.4%) all-cause deaths in the ibrutinib-venetoclax and chlorambucil-obinutuzumab arms, respectively. CONCLUSIONS: Ibrutinib-venetoclax, an all-oral, once-daily, fixed-duration combination, demonstrated superior PFS and deeper and better sustained responses versus chlorambucil-obinutuzumab as first-line CLL treatment in older patients and/or those with comorbidities. (Funded by Janssen Research & Development, LLC, and Pharmacyclics; ClinicalTrials.gov number, NCT03462719.)
Keywords: komorbidita; lidé; Middle Aged; Adult; Female; Antineoplastic Agents; Pyrazoles; protinádorové látky; Humans; pyrimidiny; protokoly protinádorové kombinované chemoterapie; Piperidines; Comorbidity; lidé středního věku; mužské pohlaví; mladý dospělý; pyrazoly; adenin; ženské pohlaví; Young Adult; piperidiny; Aged, 80 and over; senioři nad 80 let; Male; Aged; chronická lymfatická leukemie; dospělí; Adenine; Pyrimidines; Antineoplastic Combined Chemotherapy Protocols; Leukemia, Lymphocytic, Chronic, B-Cell; senioři